Analysis of Public Relations Problems in Al-Falah Elementary School - Endah Parawangsa; Risfa Khoerunisa Harliani; Tin Rustini (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Public relations has an important role in school organizations, but there are many problems in implementing the roles and functions of public relations at Al-Falah Elementary School. This will be the focus of study in this research. This research uses a qualitative approach, in which the researcher tries to describe what happened in the field (field facts) into a narrative. public relations has roles and functions including as a mediator with external parties, promoting the existence of schools and maintaining harmony with the community by sticking to the eight principles of public relations. As for carrying out his public relations duties at Al-Falah Elementary School, there are three main problems in carrying out their roles and functions, namely multiple positions, miscommunication and lots of extortion. The solution is to work with school principals, utilize technology and cooperate with authorized agencies.